Humanités numériques et formation innovante en didactique du FLE. - Jérémi Sauvage (Recherches en didactique des langues et des cultures)
The aim of this paper is to address the challenges of creating innovative training in foreign language teaching. In this case, we focus on developing a hybrid French as a Foreign Language university diploma, relying on digital devices allowing for the implementation of learning sequences accessible to the distance learner. We will insist in particular on the need to avoid misusing the term of innovation, and we will see that a pedagogy which wants to be really innovative requires a fundamental reflection not only on the pedagogic level but also on the administrative and technological fronts to be able to answer to international students’ needs regarding their mobilities.